2022
DOI: 10.1017/s0263574722000376
|View full text |Cite
|
Sign up to set email alerts
|

Study on the design and control method of a wire-driven waist rehabilitation training parallel robot

Abstract: With the increasing demand for rehabilitation and the lack of professional rehabilitation personnel, robot-assisted rehabilitation technology plays an increasingly important role in neurological rehabilitation. In order to recover the exercise ability of patients with waist injury, a new type of wire-driven waist rehabilitation training parallel robot (WWRTPR) is designed. According to the motion trajectory planning of waist rehabilitation training, two coordinate systems are established: moving coordinate sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[12]. They can be used as motion simulators [13], large-scale telescope orientation [14], large-scale camera systems [15], and construction [16], to name just a few examples even with applications to industrial scenarios as reported in [17][18][19]. CDPRs have been successfully implemented also in medical applications such as for assisting post-stroke or paraplegia patients such as reported for example in refs.…”
Section: Introductionmentioning
confidence: 99%
“…[12]. They can be used as motion simulators [13], large-scale telescope orientation [14], large-scale camera systems [15], and construction [16], to name just a few examples even with applications to industrial scenarios as reported in [17][18][19]. CDPRs have been successfully implemented also in medical applications such as for assisting post-stroke or paraplegia patients such as reported for example in refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, it still needs further improvement in multiple constraints and efficiency. Recently, artificial neural networks have been used to solve the inverse kinematics problem for robotic arms [26][27][28]. The size of the training set will vary significantly with the number of degrees of freedom, and the solution is very inefficient on a continuum robotic arm with super-redundant degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%